Impact of introduction of a rounding checklist in a pediatric intensive care unit of a developing country: A quality improvement project - Awais Abbas; Faris Abdul Aziz; Naveed Ur Rehman Siddiqui; Yasmin Hashwani; Iraj Khan; Aniqa Abdul Rasool; Anwar Ul Haque; Qalab Abbas (Wolters Kluwer Medknow Publications, 2023)
Background: Patients admitted to critical care need timely interventions after evaluating all clinical parameters. This study aims to assess the impact of the comprehensive rounding checklist on physician compliance and patient-related outcomes in a multidisciplinary pediatric intensive care unit (PICU). Subjects and Methods: This prospective observational study was conducted in two phases over period of 2 months at multidisciplinary PICU from Pakistan. A structured rounding checklist of 35 components encompassing patient care was introduced and implemented in the PICU. During the preimplementation phase, a nurse took notes of relevant patient clinical details missed by the physician during the round, included them in the rounding checklist. And during the implementation phase, the nurse actively intervened when a physician did not discuss a particular component during the round. All components discussed were check marked. Results: The checklist was completed for 812 rounds (162 patients) in preimplementation and 2348 rounds (590 patients) in the postimplementation phase. Most frequently missed components in the preimplementation phase were checking for surgical site infection (8.9%), discharge plan (7.5%), deep vein thrombosis (DVT) prophylaxis (7.3%), and ventilator-associated pneumonia bundles (7.0%). Whereas, during the postimplementation phase, resident teaching (8.0%), discharge plan (7.2%), and DVT prophylaxis (6.5%) were most frequently missed. Hospital length of stay decreased from 4.5 ± 3.7 to 4.1 ± 2.9 days (P = 0.05), and overall mortality decreased from 19% to 11.4% (P < 0.05). Conclusions: Introducing the checklist with a prompter, improved physician compliance and patient-related outcomes in our PICU.